Characterization of Short Time Marine Corroded Surfaces. Issue 14 (7th October 2019) - Poon, Jeffrey; Collins, Sean M.; Madden, David C.; Sonke, Hans; Clarke, Stuart M.
Abstract : This work investigates the corrosion of offshore structural steel surfaces over particularly short timescales. The focus is on the short-term effects between surface treatment and coating application (typically several hours). Offshore structures are exposed to an aggressive marine environment, where substrates will be contaminated by aerosols containing salts within hours, even under mild weather conditions. Localised corrosion studies of the anodic and cathodic regions of S355 steel surfaces undergoing salt drop corrosion are characterised. Significantly, the corrosion products are found to grow rapidly and are inhomogeneous, porous, and amorphous. They evolve to higher oxidation state oxides quickly with corrosion time. Therefore, microscopic corrosion products will form on newly exposed substrates in marine environments, even before the protective paint is applied.